Lagenorhynchus cruciger - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
4. Hourglass Dolphin Lagenorhynchus cruciger French: Dauphin sablier / German: Sanduhrdelfin / Spanish: Delfin cruzado Other common names: Sea Skunk, Springer, Wilson's Dolphin Taxonomy. Delphinus cruciger Quoy & Gaimard, 1824, “entre la Nouvelle-Hollande et le cap Horn [= between Australia and Cape Horn].par 49 [S] de latitude,” southern Pacific Ocean. Taxonomy of Lagenorhynchus is currently in dispute; recent molecular analyses have revealed that the genus is not monophyletic. L. australis and L. cruciger appear to be most closely related to species of Cephalorhynchus and may be reassigned to this or another genus (Sagmatias) in the near future. Monotypic. Distribution. Circumpolar in subantarctic and Antarctic waters, primarily between 45° S and 65° S, but occasionally recorded N up to 33° S off Chile. Descriptive notes. Total length 160-190 cm (males) and 140-180 cm (females); weight up to 94 kg (males) and up to 88 kg (females). Neonates are ¢.100 cm long. The Hourglass Dolphin has robust body shape with short but well-defined beak. Dorsal fin is medium-sized and characteristically hooked in shape. In some individuals, mostly adult males, dorsal fin’s leading edge is bent backward. Males also have more keeled tailstock. Back and flanks are black, and belly and throat are white. Flanks are marked by wide white streaks that extend from base of flukes, arch over upper onehalf of body, and descend along sides of head to mouth in front of eyes, converging with white lower jaw and throat. Flank streaks taper into a thin white line mid-body just below dorsal fin, creating characteristic hourglass shape. Just in front of urogenital area, white belly pigmentation intrudesslightly into black pigmentation of lower lateral tailstock in the shape of a small hook. Dorsal fin, flippers, and flukes are black on both sides. Immature individuals have less pronounced hooks in dorsal fins and have more muted color pattern. There are 26-34 pairs of slender, conical teeth in upper jaw and 27-35 pairs in lower jaw. Habitat. ...